Pengaruh Kualitas Pelayanan, Persepsi Harga, Dan Citra Merek Terhadap Kepuasan Tamu Di Favehotel Gatot Subroto Jakarta - Maesaroh, Maesaroh; Hadisuwarno, Hariadi (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2022)
This research aims to analyze service quality, price perception, and brand image on guest satisfaction at Favehotel Gatot Subroto Jakarta. The type of data used is primary data in the form of respondents' opinions by distributing questionnaires. The population in this study is the customer of Favehotel Gatot Subroto Jakarta with a sample of 107 respondents by purposive sampling. The data obtained will be analyzed using quantitative methods with multiple linear regression analysis. Based on the research that has been done, the results show that the service quality variable, either simultaneously or partially, has a positive and significant effect on guest satisfaction, the price perception variable, either simultaneously or partially, has a positive and significant effect on guest satisfaction, and the brand image variable either simultaneously or partially. partial positive and significant effect on guest satisfaction.